Microfinance Risk Measurement Framework at the Blue Nile Foundation for Microfinance in Sudan - Abdullah, Shahabuddin Mohammed Ahmed (Journal of Economic, Administrative and Legal Sciences, 2017)
The study aims to develop a framework for measuring microfinance institution in the Blue Nile in Sudan Microfinance risk. The study data collected from the Blue Nile Foundation Microfinance database. The study sample consisted of 434 individuals, 217 of them tripped and 217 not tripped. This sample used in the development of microfinance as part of measures the risk. Results of the study showed that the use of a binary logistic regression response (Regression- binary logistic) made it possible to develop a framework to measure the risks of microfinance. The possibility of overall error in this model 5.5%, and this shows the data model explains a good explanation. This confirms the goodness of fit of the model fully. It was also suggested a form to collect data on asylum microfinance, to help in forecasting the various risks.